Analisis Expected Return Dan Risiko Portofolio Sebelum Dan Pada Saat Pandemi Covid-19 Pada Saham LQ-45 - Wiwit Hariyanto; Fityan Izza Noor A; Sarwenda Biduri (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2022)
This study aims to determine whether there are differences in the Expected Return and Risk of the LQ-45 Stock Portfolio before and during the COVID-19 pandemic. This type of research is quantitative research. The object of this research is LQ-45 stock in 2019-2020 or during and before the COVID-19 pandemic. The conclusion in this study is that the portfolio in this study uses the Markowitz Portfolio model which forms a combination into 21 combinations in the 2019-2020 time interval. From the results of the combination, it was found that the Expected Return and Portfolio Risk levels in the composition of 50:50 and 70:30 experienced differences before and during the COVID-19 pandemic.